The Church of Our Saviour in Berestovo: Between the Architectural Trends of Kiev and Polotsk in the Late 11th and 12th Century - Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2021)
The article considers the Church of Our Saviour in Berestovo (Kiev) in terms of its place in the early Russian architecture of the premongol period. Several outstanding architectural features point us to the architecture of Polotsk, namely the cross-shaped layout arranged with porticoes, the trefoil shape of the portico vaulting, and the recessed brickwork without applying the rubble stone courses. The degree of innovation embodied in these features however is defined by the dating of the church, which differs much in the recent literature, from 1060s to 1120s. The new observations on the brick features and foundations technology made on the base of the field documentation of the excavations of 1914, 1989–1991, and 2003 expand the characteristic of the building methods used for the construction of the church and lead to the conclusion that only approximate dating (late 11th — early 12th century) is possible. This dating has an importance in defining the chronology of the architecture of Polotsk.This research has been completed with the support of the Russian Foundation of Basic Research, project № 19-012-00311 “St. Sophia cathedral in Polotsk. The building, its history and architecture. Materials of archaeological exploration, 1970–1980-ies”.
Keywords: Byzantine architecture; architecture of Early Rus`; Old Kiev; Berestovo; trefoil shape; cross-shape layout; stripe foundations; bricks; Polotsk architecture